Experimental Investigation on Short Concrete Columns Reinforced by Bamboo Scrimber under Axial Compression Loads - Min Lei; Zihao Wang; Penghui Li; Liyi Zeng; Hongyao Liu; Zhidong Zhang; Huicheng Su (Advances in Civil Engineering)
The paper presents bamboo scrimber bars as a reinforcing material instead of steel reinforcement in low-strength concrete columns. Twelve short concrete columns with different reinforcements are tested under axial compression load to study the axial compressive behavior of short concrete columns reinforced by bamboo scrimber. Three columns are reinforced concrete columns, and the other nine columns are bamboo scrimber reinforced concrete columns. The failure process, bearing capacity, axial deformation, and strain of the specimens are compared and analyzed. The results show that the bonding performance between the bamboo scrimber bars by surface treatment and low-strength concrete is excellent. In low-strength concrete columns, the material properties of bamboo bars play more thoroughly than those of steel bars. When the bamboo reinforcement ratio is increased, the concrete column ductility is significantly improved, but the bearing capacity of the concrete column is not increased. The bamboo scrimber bars with the size of 10 mm × 10 mm or 15 mm × 15 mm can be used as longitudinal bars of low-strength concrete columns. The ductility of the short concrete column with 2.56% bamboo scrimber reinforcement is close to that of the short concrete column with 0.72% steel reinforcement.